The Use of German Linduo HD Application as Independent Learning Media for Class XI IBB Students of SMA Laboratorium UM - Minchatus Salwa (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2021)
The purpose of this study is to describe the use of German Linduo HD as independent learning media and students responses to the application, also the obstacles while using the application by students of class XI IBB SMA Laboratorium UM. In carrying out this study, the researchers used qualitative descriptive method. The data resource for this study was 31 students in class XI IBB SMA Laboratorium UM. Interview and documentation were the instrument used by researcher for data collection. The results showed that most students are able to operate the application well. Based on the results of the interviews, students felt that illustrations in the application and also fun song accompaniments help make it easier for students to understand German material. On the other hand, there are difficulties when using this application, namely unclear usage directions in operating the application and difficulty in operating in writing practice section.